Tracking the amphibian pathogens Batrachochytrium dendrobatidis and Batrachochytrium salamandrivorans using a highly specific monoclonal antibody and lateral-flow technology - Dillon, MJ; Bowkett, AE; Bungard, MJ; Beckman, KM; O'Brien, MF; Kieran Bates; Fisher, MC; Stevens, JR; Thornton, CR (Wiley, 2016)
The fungus Batrachochytrium dendrobatidis (Bd) causes chytridiomycosis, a lethal epizootic disease of amphibians. Rapid identification of the pathogen and biosecurity is essential to prevent its spread, but current laboratory‐based tests are time‐consuming and require specialist equipment. Here, we describe the generation of an IgM monoclonal antibody (mAb), 5C4, specific to Bd as well as the related salamander and newt pathogen Batrachochytrium salamandrivorans (Bsal). The mAb, which binds to a glycoprotein antigen present on the surface of zoospores, sporangia and zoosporangia, was used to develop a lateral‐flow assay (LFA) for rapid (15 min) detection of the pathogens. The LFA detects known lineages of Bd and also Bsal, as well as the closely related fungus Homolaphlyctis polyrhiza, but does not detect a wide range of related and unrelated fungi and oomycetes likely to be present in amphibian habitats. When combined with a simple swabbing procedure, the LFA was 100% accurate in detecting the water‐soluble 5C4 antigen present in skin, foot and pelvic samples from frogs, newts and salamanders naturally infected with Bd or Bsal. Our results demonstrate the potential of the portable LFA as a rapid qualitative assay for tracking these amphibian pathogens and as an adjunct test to nucleic acid‐based detection methods.